Collective Bargaining by Salaried Professionals - Adams, Georges W. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This paper examines whether the traditional approach to collective bargaining fit s the needs of the salaried professionals or if special treatment is necessary.